A study of optimal resources allocation models for the Northern Ireland economy - Glass, J. C.; Kiountouzis, E. (Statistical and Social Inquiry Society of Ireland, 1974)
To aid the development of plans for Northern Ireland, economists have been concerned with the formulation of various types of models. A significant contribution in this respect is the recent construction of input-output tables for Northern Ireland. These tables have opened a new avenue for building descriptive and quantitative models of the Northern Ireland economy, they permit important inter-industry analysis, on a detailed basis and, in addition, provide a consistent framework for multiplier analysis and forecasting .
Read before the Society, 6 May 1974
Keywords: Optimal resource allocation; Economic planning; Economic development; Linear programming models; 314.15